The scenes of crime in five cities (1999)
Information obtained from a sample of 223 male offenders between the ages of 18 and 29 consecutively identified in five cities in Colombia indicate that the majority of the offenses reported occurred between Friday and Sunday, during the day, in the street and involved strangers. Property offenses were most frequently reported. Only 33 % and 13 % of the offenses were committed after consuming alcohol or drugs.